Conversational Implicature of Peanuts Comic Strip Based on Grice’s Maxim Theory - Muhartoyo Muhartoyo; Sistofa Sistofa (Bina Nusantara University, 2013)
This article discusses about conversational implicature that occurs in Peanuts comic strips. The objectives of this study are to find out the implied meaning in the conversation between Charlie Brown with Lucy van Pelt and Lucy van Pelt with Linus van Pelt to evaluate the existence of maxim flouting and maxim violating in those conversations in relation to the four maxims such as quantity, quality, relation, and manner. Likewise, this study attempts to find out the reason for using conversational implicature in a comic strip. The writers uses a qualitative method with library research concerning to Grice’s maxim theory to analyze the conversational implicature. Based on the analysis, it can be concluded that all the comics that comprise 14 comics generate conversational implicature since all the characters breach rules of maxim. The result of this analysis shows that flouting maxim of manner has the highest occurrence of conversational implicature and the least occurrences belong to flouting maxim of relation and violating maxim of quantity. Moreover, the writers concludes that to make a successful communication ideally the speaker and the hearer to cooperate in the conversation by saying explicitly so the hearer can grasp the meaning as the goal of communication is to deliver a message to the hearer.